Liver transplantation outcomes after transarterial chemotherapy for hepatocellular carcinoma. Issue 9 (28th March 2020) - Wallace, D.; Cowling, T. E.; Walker, K.; Suddle, A.; Gimson, A.; Rowe, I.; Callaghan, C.; Sapisochin, G.; Mehta, N.; Heaton, N.; van der Meulen, J.
Abstract : Background: Transarterial chemoembolization (TACE) in patients with hepatocellular carcinoma (HCC) awaiting liver transplantation is widespread, although evidence that it improves outcomes is lacking and there exist concerns about morbidity. The impact of TACE on outcomes after transplantation was evaluated in this study. Methods: Patients with HCC who had liver transplantation in the UK were identified, and stratified according to whether they received TACE between 2006 and 2016. Cox regression methods were used to estimate hazard ratios (HRs) for death and graft failure after transplantation adjusted for donor and recipient characteristics. Results: In total, 385 of 968 patients (39·8 per cent) received TACE. Five‐year patient survival after transplantation was similar in those who had or had not received TACE: 75·2 (95 per cent c.i. 68·8 to 80·5) and 75·0 (70·5 to 78·8) per cent respectively. After adjustment for donor and recipient characteristics, there were no differences in mortality (HR 0·96, 95 per cent c.i. 0·67 to 1·38; P =  0·821) or graft failure (HR 1·01, 0·73 to 1·40; P =  0·964). The number of TACE treatments (2 or more versus 1: HR 0·97, 0·61 to 1·55; P =  0·903) or the time of death after transplantation (within or after 90 days; P =  0·291) did not alter the outcome. The incidence of hepatic artery thrombosis was low in those who had or had not received TACE (1·3 and 2·4 per cent respectively; P =  0·235). Conclusion: TACE delivered to patients with HCC before liver transplant did not affect complications, patient death or graft failure after transplantation. Abstract : The impact of transarterial chemoembolization (TACE) on oncological outcomes and postoperative complications in the UK is not well characterized. Patients with hepatocellular carcinoma who were recipients of a liver transplant were stratified according to whether they received TACE, and its impact on post‐transplant mortality, graft failure and postoperative complications was assessed. The use of TACE before liver transplantation did not significantly affect the risk of post‐transplant complications, mortality or graft failure. No influence on outcomes Abstract : Antecedentes: La quimioembolización transarterial ( transarterial chemoembolization, TACE) en pacientes con carcinoma hepatocelular ( hepatocellular carcinoma, HCC) se utiliza como puente al trasplante hepático, aunque falta evidencia de que mejore los resultados y la morbilidad relacionada es motivo de preocupación. En este estudio se evaluó el impacto de la TACE en los resultados tras el trasplante para analizar las complicaciones. Métodos: Se identificaron los receptores de trasplante hepático por HCC en el Reino Unido y se estratificaron según si habían recibido TACE entre 2006 y 2016. Se utilizó el método de regresión de Cox para estimar los cocientes de riesgos instantáneos ( hazard ratio, HR) para la mortalidad post‐trasplante y el fallo del injerto ajustados por las características del donante y del receptor. Resultados: En total, 385 (39, 8%) de 968 pacientes recibieron TACE, observándose similar supervivencia del paciente a los 5 años después del trasplante: 75, 2% (i.c. del 95%: 68, 8% a 80, 5%) con TACE y 75, 0% (70, 5% a 78, 8 %) sin TACE. Después de ajustar según las características del donante y del receptor, no hubo diferencias en la mortalidad (HR: 0, 96, 0, 67 a 1, 38; P = 0, 82) o en el fallo del injerto (HR: 1, 01, 0, 73 a 1, 40; P = 0, 96). El número de tratamientos con TACE (≥ 2 tratamientos TACE HR: 0, 97, 0, 61 a 1, 55; P = 0, 90) o el período de tiempo después del trasplante (mortalidad del paciente antes o después de 90 días; P = 0, 29) no alteró el resultado. La incidencia de trombosis de la arteria hepática fue baja en aquellos que recibieron TACE o no (1, 3% y 2, 5%, respectivamente; P = 0, 23). El fallo del injerto debido a eventos oclusivos fue similar en el grupo de pacientes que recibieron TACE (8, 0% o 11/137) o que no la recibieron (6, 7% o 5/75) TACE ( P = 0, 74). Conclusión: La administración de TACE en pacientes con HCC antes del trasplante hepático no influyó en las complicaciones post‐trasplante, la mortalidad del paciente o el fallo del injerto.